Evaluation of the Success of Transportation Infrastructure Renewal Projects: Case Study of the Jakarta-Bandung High-Speed Train Development - Hayati, Amelia; Sulaksana, Rahadi Meta Tri; Wardani, AAA Made Cahaya; Raharja, Adyk Marga (Journal of Renewable Engineering, 2025)
The development of transportation infrastructure has a multidimensional impact in driving economic growth and regional integration. The Jakarta-Bandung High-Speed Rail project is expected to reduce traffic congestion and improve connectivity and mobility efficiency. However, its success must be assessed not only from the technical aspects and physical completion, but also the effectiveness of public investment, long-term economic impacts, and environmental sustainability. The main challenges of this project include land acquisition, financial uncertainty due to debt-based financing schemes, and integration with other transportation systems. From a social perspective, this project has the potential to drive urbanization around the route, but also poses the risk of development inequality and gentrification. Ecological impacts are also a concern, especially in terms of land degradation and operational energy consumption. This study uses a literature study method with content analysis to evaluate the success of the project based on economic, social, and environmental indicators. The results of the study show that the effectiveness of this project is highly dependent on operational optimization, integration of transportation modes, and the sustainability policies implemented. With transparent governance and appropriate risk mitigation strategies, this project has the potential to provide long-term benefits for economic growth and community welfare, as well as being a model for more inclusive and sustainable transportation infrastructure development in Indonesia.